2015
DOI: 10.1002/rra.2898
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of Stream Crossing Traffic On Macroinvertebrate Communities in the Missouri Ozark River

Abstract: Depending on intensity, physical disturbance can either decrease or increase diversity of stream macroinvertebrate communities. Recreational activities in parks are one component of physical disturbance. Our objective was to evaluate the effects of stream crossings and recreational traffic on macroinvertebrate assemblages. Five stream-crossing sites were sampled during winter and summer in the Current River, Ozarks National Scenic Riverways, Missouri, USA. Stream-crossing traffic was assessed using trail camer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 27 publications
4
11
0
Order By: Relevance
“…Our results are consistent with others [19,20] who found that trampling as a result of outdoor recreational use did not impact aquatic macroinvertebrates in streams in Utah and Missouri. Our results contradict the results of experimental simulations and field studies that have documented declines in taxa richness, abundance and the abundances of selected populations and guilds within streams in the United States, Brazil and Australia [13][14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are consistent with others [19,20] who found that trampling as a result of outdoor recreational use did not impact aquatic macroinvertebrates in streams in Utah and Missouri. Our results contradict the results of experimental simulations and field studies that have documented declines in taxa richness, abundance and the abundances of selected populations and guilds within streams in the United States, Brazil and Australia [13][14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 93%
“…Studies that did not document trampling impacts were conducted in the United States and those documenting trampling impacts were conducted in the United States [15][16][17][18] and internationally [13,14]. Studies in both categories were conducted in a range of stream sizes from small streams (i.e., first or second order) (our study, [17,18]) to larger wadeable streams [13][14][15][16]19,20]. Studies in both categories spanned a range of methods including those consisting of simulated experimental trampling (our study, [13,14]) and field studies that sampled sites with different levels of trampling or sampled above and below stream crossings [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations